Depth-distribution patterns of demersal fishes of the Samar Sea, Philippines and their use for estimation of mortality - Sambilay, Victor C., Jr (College of Fisheries, U. P. in the Visayas, 1991)
A method for estimating total mortality (Z), proposed by D. Pauly, the "pseudo catch curve", which relies on a positive correlation between mean fish size and water depth, is tested with regard to the validity of estimates derived from itThe distribution with respect to depth of different size-groups of ten demersal fish species from the Samar Sea, Philippines were established based on length-frequency and catch/effort data from trawl surveys conducted from March 1979 to May 1980. Relationships linking size and depth along with a discussion of some of the factors explaining these patterns, and estimates of Z as obtained from pseudo catch curves and other methods are presented. Overall, the pseudo catch curve method appeared to provide reliable estimates of total mortality..